2018
DOI: 10.1039/c8ob00293b
|View full text |Cite
|
Sign up to set email alerts
|

Annulation of β-naphthols and 4-hydroxycoumarins with vinylsulfonium salts: synthesis of dihydrofuran derivatives

Abstract: A new synthetic approach to dihydrofuran derivatives via the annulation reaction of β-naphthols and 4-hydroxycoumarins with vinylsulfonium salts has been developed. A variety of dihydrofuran derivatives were prepared in moderate to good yields under mild conditions. The products could be readily transformed to the corresponding furans via the dehydrogenation with DDQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Another recent example of an annulation with carbon nucleophiles was published in 2018 by Yan et al (Scheme 83c). 310 Therein, the annulation of naphthols and 4-hydroxycoumarins to form a range of dihydrofurans was accomplished in good yields. In this case, the authors propose an electrophilic aromatic substitution as the first step; subsequent cyclization affords dihydrofurans, which can be oxidized by DDQ to the respective furan derivatives.…”
Section: Sulfonium Saltsmentioning
confidence: 99%
“…Another recent example of an annulation with carbon nucleophiles was published in 2018 by Yan et al (Scheme 83c). 310 Therein, the annulation of naphthols and 4-hydroxycoumarins to form a range of dihydrofurans was accomplished in good yields. In this case, the authors propose an electrophilic aromatic substitution as the first step; subsequent cyclization affords dihydrofurans, which can be oxidized by DDQ to the respective furan derivatives.…”
Section: Sulfonium Saltsmentioning
confidence: 99%
“…The formation of the products can be rationalised by assuming the known behaviour of stabilised sulphonium ylides towards system bearing an electrophilic centre and a nucleophilic heteroatom. 65 The work of Yan et al 66 demonstrated that annulation reaction of b-naphthols with (2-bromoethyl)diphenylsulfonium tri-uoromethanesulfonate salt (158) in the presence of K 2 CO 3 in CH 3 CN at 0 C under an argon atmosphere for 16-24 h led to the formation of dihydronaphthofurans 159 in moderate to good yields (54-92%) (Scheme 75). A tentative reaction mechanism is outlined in Scheme 76.…”
Section: Transition-metal Catalyzed Synthesismentioning
confidence: 99%
“…The construction of furocoumarin derivatives has been reported. However, the current synthesis toward this skeleton is limited, involving harsh conditions, expensive catalysts, microwave-mediated reactions, and unsatisfactory yields (Figure ). Chênevert et al previously reported a synthetic route for a furo­[3,2- c ]­coumarin derivative 3,3-dimethyl-2-methylene-2,3-dihydro-4 H -furo­[3,2- c ]­chromen-4-one, which also required a high reaction temperature (Figure b) .…”
Section: Introductionmentioning
confidence: 99%